Aesophageal speech for a laryngectomee - Srinivas Gudi (Journal of All India Institute of Speech and Hearing, 1970)
Mr A., reported to the clinic on 2-8-1968. He was 52 years old, and a peasant by occupation. He was referred to the clinic from the Cancer Institute, Madras for speech therapy